Life-conditions and anthropometric variables as risk factors for oral health in children in Ladakh, a cross-sectional survey - Maria Grazia Cagetti; Fabio Cocco; Ezio Calzavara; Davide Augello; Phunchok Zangpoo; Guglielmo Campus (BMC, 2021)
Abstract Background The aim of this survey was to evaluate the severity of dental caries among children living in Zanskar Valley (Ladakh, India) and its association with anthropometric and background variables. Methods This cross‐sectional survey was conducted on schoolchildren divided into four age groups (< 6, ≥ 6 < 11, ≥ 11 < 14 and > 14 years of age). A total of 1474 schoolchildren (607 males, 41.2%) were examined. Actual caries prevalence (dt/DT) and gingival bleeding were recorded by four calibrated dentists. An ad hoc questionnaire evaluated general health, eating habits, oral hygiene and the self-perception of oral conditions. Height, weight, waist circumference, heart-rate and oxygen-saturation were also collected directly by examiners. Responses to questionnaire items were treated as categorical or ordinal variables. The relationship between children's caries data, gingival bleeding, gender, Body Mass Index (BMI) following the International Obesity Task Force, waist circumference and questionnaire items was assessed using the Kruskal-Wallis test and Pearson correlation. Conditional ordinal logistic regression was used to analyse associations among caries severity, gender, BMI, waist circumference, oxygen saturation and questionnaire items. A forward stepwise logistic regression procedure was also carried-out to estimate the ORs of gingival bleeding prevalence and the covariates derived from examination or questionnaire. Results Caries was almost ubiquitarian with only 10.0% of caries-free children (dt/DT = 0). Caries severity, in both primary and permanent dentitions, was statistically significantly related to gender, waist circumference, BMI, oral hygiene frequency and self-reported chewing problems (p < 0.01 in both dentitions). An increasing relative risk for caries in permanent dentition compared to caries-free subjects was observed in children with a low BMI (RRR = 1.67, 95%CI = 1.54/2.83 for subjects with 1-3 caries lesions and RRR = 1.52, 95%CI = 1.36/1.74 for subjects with > 3 caries lesions); also, children with reduced waist circumference had a higher relative risk to have 1-3 caries lesions (RRR = 2.16, 95%CI = 1.84/2.53) and an even higher risk to have more than 3 caries lesions (RRR = 4.22, 95%CI = 3.33/5.34). Conclusions A significant impact of untreated caries lesions was observed in Ladakh schoolchildren; low BMI values and reduced waist circumference showed to be the main caries risk predictors. Preventive and intervention programmes should be implemented to improve children's oral health.